DEVELOPMENT OF HTML5 FLIP-ASSISTED ELECTRONIC MODULE CULTURAL HERITAGE MATERIAL FOR GRADE 5 ELEMENTARY SCHOOL STUDENTS - Nahdhiah, Umi; Untari, Sri; Ekawati, Ratna (Universitas Muhammadiyah Mataram, 2025)
Education is a crucial means of passing on culture. This research aims to develop a valid HTML5 Flip-assisted e-module for learning cultural heritage materials, intended for grade 5 elementary school students. This research uses the Research and Development (R&D) method of Richey and Klein model which consists of three stages, namely planning, production, and evaluation. Participants in this study consisted of one elementary school teacher and one instructional designer as validators of material experts and media experts. The results showed that the Flip HTML5-assisted e-module is very valid to be used as a learning medium. Material expert validation obtained a score of 96% and was categorized as very valid, while media expert validation obtained a value of 89% which means very valid. Thus, this e-module can be an alternative innovative learning media that is feasible to be implemented in primary education.